Sociocultural Patterns: Child Rearing Styles in an Amuesha Community in the Central Jungle of Peru - Herrera Álvarez, Angela María; Venegas-Mejía , Valia; Esquivel-Grados, José; Lavado Guzmán, Milagritos; M.Villamar, Roger (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The upbringing of infants in native communities is the concern of authorities and researchers for being a vulnerable population segment. The purpose of the study was to analyze child rearing styles of an Amuesha community in the Peruvian jungle. The phenomenological design allowed interviewing amuesha mothers from Oxapampa in Pasco, until reaching saturation. It was found as results that child rearing practices conform to sociocultural patterns, such as identity and communal heritage culture, which are in extinction due to the presence of exotic factors; in addition to a demand to the State for better education and health services.